Small-Incision Lenticule Extraction for Myopia. Issue 1 (January 2015) - Xu, Yesheng; Yang, Yabo
ABSTRACT Purpose To analyze the safety, efficacy, stability, and predictability of small-incision lenticule extraction to correct myopia. Methods Patients were evaluated preoperatively and then at 1 day, at 2 weeks, and at 1, 3, 6, and 12 months postoperatively. Safety, efficacy, stability, predictability, and surgical complications were assessed. Changes in higher-order aberrations, intraocular pressure, central corneal thickness, dry eye signs, contrast sensitivity, and subjective glare symptoms were evaluated. Results All 52 myopic patients in the initial treatment group completed the final 12-month follow-up. At 12 months, 90.4% of eyes were within ±0.5 diopters (D) of the intended refractive target. The mean (±SD) change in manifest refraction from 1 day to 12 months was −0.06 (±0.37) D. The uncorrected visual acuity was better than or equal to 20/20 in 83% of eyes; 98% of eyes had a best-corrected visual acuity of better than or equal to 20/20. No eye lost two or more Snellen lines. There was an increase in higher-order aberrations, spherical aberration, and coma postoperatively. No significant increase in intraocular pressure occurred. The tear breakup time decreased significantly after surgery and did not return to preoperative levels within 12 months. The log contrast sensitivity value with glare of 6.3, 4.0, 2.5, and 1.6 degrees of visual angle at 1 month was statistically significantly reduced but recovered to preoperative levels after 3 months. Twenty-seven percent of patients complained of mild or moderate glare postoperatively, but the symptoms disappeared during the 12-month follow-up period with no influence on daily life. No vision-threatening complications occurred. Conclusion Small-incision lenticule extraction is a promising corneal refractive procedure to correct myopia.